ANALYSIS OF THE CONSUMPTION BEHAVIOUR OF HALAL PRODUCTS AMONG BAGANSIAPIAPI COMMUNITY IN ROKAN HILIR REGENCY - Any Widayatsari; Nobel Aqualdo; CUT ENDANG KURNIASIH (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2022)
This study aims to investigate the factors that influence consumer behavior in purchasing halal products at Bagansiapiapi such as understanding the halal label, social factors and purchase intentions. This research is a qualitative research, with a descriptive approach. The sample selection technique used is a purposive sampling technique of 50 informants. The results showed that the public's understanding of halal products in Bagansiapiapi is quite high. Environmental and family factors have an important influence on consuming halal-labeled food. Meanwhile, the purchase intention variable towards the purchase of products, respondents prefer to consume packaged food labeled halal compared to non-halal products. It is expected that the findings of this study is for the business to consider adding halal labels on their products and need support from LPPOM MUI and health experts to educate the public about the importance of healthy and halal food